Classification of very low birth weight infants as small for gestational age: International vs. national standards - Marta Tejón-Fernández; Ana Isabel Armenteros-López; Nazareth Fernández-Rosales; Javier Díez-Delgado; Diego Salagre; Rafael Galera-Martínez; Manuel Martin-González; Antonio Bonillo-Perales (PLoS ONE, 2025)
Background It is not precisely known whether the use of national (Carrascosa 2008) and international growth standards (INTERGROWTH-21) shows good concordance in classifying very low birth weight infants as small-for-gestational-age or whether with the same degree of morbidity and mortality. The aims of this study were a) to evaluate the concordance between small-for-gestational-age neonates weighing <1500 g classified using the national and international standards, and b) to compare the morbidity and mortality of small-for-gestational-age neonates classified by both standards. Methods A retrospective cohort study was conducted with very low birth weight infants. The concordance between the INTERGROWTH-21 and Carrascosa 2008 standards was analyzed, along with differences in gestational age, weight, medical requirements, morbidity, and mortality, among small-for-gestational-age neonates classified by both standards. Small-for-gestational-age was defined as a birth weight z score ≤ −1.28. Results A total of 250 neonates weighing <1500 g, who were born between 26 and 36 weeks of gestation, were included. There was a high level of concordance in the classification of small-for-gestational-age between the two standards (Cohen’s kappa = 0.80, p < 0.001). A lower incidence was observed when the INTERGROWTH-21 standard was used (31.6%) compared to the Carrascosa 2008 standard (40.8%), p = 0.03. No significant differences were found in mortality or morbidity among neonates classified as small-for-gestational-age by both standards. Conclusion The Carrascosa 2008 and INTERGROWTH-21 standards classify small-for-gestational-age infants with comparable morbidity and mortality. We recommend the use of the INTERGROWTH-21 standard for its inclusion of multiple pregnancies, diverse ethnicities, and international comparability.